2012
DOI: 10.3109/00207454.2011.619285
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry and123I-DaTSCAN imaging in Parkinson's Disease: A Comparison Study

Abstract: The purpose of this study was the evaluation of pupil light reflex (PLR) in patients with Parkinson's disease (PD) by using a modern pupillometry system and the investigation of its potential relationship with dopamine transporter imaging (DaTSCAN), which is an objective method for the evaluation of presynaptic dopaminergic system. PLR was evaluated using pupillometry in 35 patients with PD without clinical evidence of autonomic dysfunction and 44 healthy matched controls. PLR was elicited using a fully automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…There is an established body of evidence to indicate that cholinergic hypofunction is a significant component of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s diseases, which are due to ACh and dopamine deficiencies, respectively. Moreover, the majority of studies that analysed ACh-dependent PLR parameters have revealed significant differences between normal age-matched patients and those with Alzheimer’s [ 55 , 56 , 57 , 72 , 73 , 74 ] or Parkinson’s disease [ 58 , 59 , 75 ]. Studies typically used light stimuli wavelength of 820 nm with a light intensity of 24.6 cd/m 2 .…”
Section: Clinical Applications Of Pupillometrymentioning
confidence: 99%
See 1 more Smart Citation
“…There is an established body of evidence to indicate that cholinergic hypofunction is a significant component of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s diseases, which are due to ACh and dopamine deficiencies, respectively. Moreover, the majority of studies that analysed ACh-dependent PLR parameters have revealed significant differences between normal age-matched patients and those with Alzheimer’s [ 55 , 56 , 57 , 72 , 73 , 74 ] or Parkinson’s disease [ 58 , 59 , 75 ]. Studies typically used light stimuli wavelength of 820 nm with a light intensity of 24.6 cd/m 2 .…”
Section: Clinical Applications Of Pupillometrymentioning
confidence: 99%
“…Studies typically used light stimuli wavelength of 820 nm with a light intensity of 24.6 cd/m 2 . Specifically, patients with Alzheimer’s [ 57 ] or Parkinson’s disease, with or without any detectable cognitive deficits or psychiatric disorders [ 55 , 57 , 75 ], had significantly lower MCV and MCA values. Ferrario et al [ 76 ] did not observe a significant difference in MCA between Alzheimer’s patients and controls; however, this may be attributed to the longer light stimulus used (1 s) compared to the other studies (20–150 ms) [ 77 ].…”
Section: Clinical Applications Of Pupillometrymentioning
confidence: 99%
“…С помощью пупиллометрии (метода регистрации величины зрачка и динамики ее изменения) при БП показано значительное снижение скорости констрикции гладких мышц радужки и ускорения сужения зрачка в ответ на световой стимул [95]. Интересно, что эти изменения более выражены при БП с когнитивными нарушениями, чем без них [96]. Важно подчеркнуть, что для БП характерна гиперреакция зрачка в ответ на парасимпатомиметические и симпатомиметические воздействия [97], что, вероятно, может быть использовано в качестве маркеров доклинической стадии БП и оценки эффективности проводимой терапии [98].…”
Section: передний отдел глаза при бпunclassified
“…It was shown using pupillometry (a method for recording the pupil size and the dynamics of its change) that the rate of constriction of the smooth muscles of the iris is significantly decreased, and that pupil constriction in response to light stimulus is accelerated in patients with PD [ 95 ]. Interestingly, these changes are more pronounced in patients with PD accompanied by cognitive impairment than without [ 96 ]. It is important to emphasize that hyperreaction of the pupil to parasympathomimetic and sympathomimetic effects is characteristic of PD [ 97 ], something that can probably be used to identify markers of a preclinical stage of PD and assess treatment effectiveness [ 98 ].…”
Section: Vision Disorders During Pd: Clinical Manifestations and Cmentioning
confidence: 99%
“…У больных БП изменены параметры реакции зрачка в ответ на различные стимулы, что было измерено с помощью пупиллометрии [17]. Отмечено значительное снижение максимальной скорости констрикции и максимального ускорения сужения зрачка на световой стимул.…”
Section: патология зрения при болезни паркинсонаunclassified